2023
DOI: 10.1038/s42003-023-04768-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokimera GIL-11 rescued IL-6R deficient mice from partial hepatectomy-induced death by signaling via non-natural gp130:LIFR:IL-11R complexes

Abstract: All except one cytokine of the Interleukin (IL-)6 family share glycoprotein (gp) 130 as the common β receptor chain. Whereas Interleukin (IL-)11 signal via the non-signaling IL-11 receptor (IL-11R) and gp130 homodimers, leukemia inhibitory factor (LIF) recruits gp130:LIF receptor (LIFR) heterodimers. Using IL-11 as a framework, we exchange the gp130-binding site III of IL-11 with the LIFR binding site III of LIF. The resulting synthetic cytokimera GIL-11 efficiently recruits the non-natural receptor signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
(157 reference statements)
0
6
0
Order By: Relevance
“…Recently, an chimeric cytokine was created by grafting the LIFR binding residues of LIF onto Site III of IL-11 to create a molecule that binds and signals through the non-natural interaction of IL-11R/LIFR/gp130. 54 This work further demonstrates the modular nature of the IL-6 family binding epitopes and the overlaps that key residues have in creating the same interactions on different scaffolds.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Recently, an chimeric cytokine was created by grafting the LIFR binding residues of LIF onto Site III of IL-11 to create a molecule that binds and signals through the non-natural interaction of IL-11R/LIFR/gp130. 54 This work further demonstrates the modular nature of the IL-6 family binding epitopes and the overlaps that key residues have in creating the same interactions on different scaffolds.…”
Section: Discussionmentioning
confidence: 66%
“…This indicates that while CLCF1 and IL‐11 have only 28% sequence homology and leverage different receptor binding partners, similarities can be drawn in terms of their key coreceptor binding regions. Recently, an chimeric cytokine was created by grafting the LIFR binding residues of LIF onto Site III of IL‐11 to create a molecule that binds and signals through the non‐natural interaction of IL‐11R/LIFR/gp130 54 . This work further demonstrates the modular nature of the IL‐6 family binding epitopes and the overlaps that key residues have in creating the same interactions on different scaffolds.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, a chimeric cytokine based on IL-11 as a backbone could be an attractive alternative in chemotherapy-induced thrombocytopenia. As a first example, we have used IL-11 as a backbone for the transfer of site 3 from LIF and showed that the resulting GIL-11 recruits and activates the IL-6R: gp130:LIFR complex [123] (Fig. 4B).…”
Section: Synthetic Chimeric Cytokines (Cytokimera) Restrict Cellular ...mentioning
confidence: 99%
“…This demonstrates that the transfer of site 3 from the α‐receptor‐independent LIF to the α‐receptor‐dependent IL‐11 retains the α‐receptor dependence, which might also be translated to IL‐6 as a backbone with the site 3 from LIF. In mice, GIL‐11 rescued IL‐6R −/− mice from death following partial hepatectomy, making gp130:IL‐11R:LIFR signaling a potential target for liver regeneration [123]. We suggest calling these chimeric cytokines Cytokimera.…”
Section: Synthetic Chimeric Cytokines (Cytokimera) Restrict Cellular ...mentioning
confidence: 99%
“…We and others have shown that at least site 3 is principally interchangeable resulting in the chimeric cytokines (cytokimera) IC7 and GIL-11. In IC7, site 3 from CNTF was transferred to IL-6 and the chimeric cytokine activated the non-natural receptor complex consisting of IL-6R:gp130:LIFR ( 19 ), whereas the transfer of site 3 from LIF to IL-11 resulting in GIL-11 led to the assembly of the non-natural receptor complex IL-11R:gp130:LIFR ( 20 ).…”
mentioning
confidence: 99%